Eye Screening in School Children: A Rapid Way - Qamar, Abdul Rasheed (Pakistan Journal of Ophthalmology, 2006)
Purpose: A screening program was carried out in different school in Punjab to detect the children with refractive errors and refer them to nearest hospitals for treatment. Materials and Methods: The screening program was carried out through the Sight First Program of Lion’s Club International. 38575 school children in different school were screened in 3 years from 2002 to 2004. A maximum participation of the teachers and volunteer paramedical staff made it possible to screen this huge number of schoolchildren. Results. Out of total 38575 schoolchildren 2069 (5.4%) were found to have refractive errors. Conclusion: The protocol described in this paper can be used to screen a large number of children in less time and with minimal involvement of the ophthalmologist(s).